МОДЕЛЬ ВЫХОДНОЙ ЦЕПИ ГЕНЕРАТОРА РАЗРЯДНЫХ ИМПУЛЬСОВ С ПЛАЗМОЭРОЗИОННОЙ НАГРУЗКОЙ, АДЕКВАТНАЯ В ШИРОКИХ ДИАПАЗОНАХ ИЗМЕНЕНИЙ ИХ ПАРАМЕТРОВ - Шидловская, Н.А.; Захарченко, С.Н.; Черкасский, А.П. (Інститут електродинаміки НАН України, Київ, 2015)
Development of electrical models of plasma-erosive loads is analyzed and the estimation of their adequacy is given. On the basis of nonlinear model of resistance of plasma-erosive load adequate in wide ranges of change of voltage and duration of discharge pulses, in program Matlab Simulink environment the model of output circuit of the generator of pulses with such load is created and its features are described. The estimation of adequacy of the offered model is given at comparison of results of calculation of time dependences of voltage and current of discharge pulses, and also resistance of load with the data received as a result of direct experiments. Dependence of relative errors of voltage and current of the discharge pulses calculated with the account and without jet elements of an equivalent circuit of load from amplitude of their voltage is given. References 22, figures 5, table 1.